Iga Myeloma with Increased Anion Gap, Pseudo hyperphosphatemia and Pseudohyponatremia - Kapoor, Rachna; Dhawan, Gaurav; Kodali, Padmaja (Journal of Human Health Research, 2018)
A myeloma case is described with laboratory artifacts including increased anion gap, pseudohyperphosphatemia, and pseudohyponatremia. The report explains mechanisms behind paraprotein‑related assay interference and diagnostic pitfalls.
Keywords: pseudohyperphosphatemia; pseudohyponatremia